SOCIAL CAPITAL AND HARMONIZATION IN THE MIDST OF THE DIVERSITY OF THE SEDAENG COMMUNITY, TOSARI DISTRICT, PASURUAN REGENCY - Khoirul Faizin; Ali hasan Siswanto (SOSIOEDUKASI, 2026)
The Tengger community in Sedaeng Village, Tosari District, Pasuruan Regency, is known for its multicultural tradition that prioritizes interreligious tolerance, even though its residents adhere to different religions, especially Islam and Hinduism. This research aims to examine how the existence of Muslims in the midst of religious and cultural diversity can take place in harmony and how social, economic, and political value systems contribute to the formation of harmony. Using a qualitative approach based on ethnography and functional structural theory, this study examines the religious portrait of the Sedaeng community through the framework of social capital. The findings show that Tengger traditional values that contain multiculturalism, local wisdom in tolerance, and social symbols inherited through tradition, are a solid foundation for interreligious harmony. Collective beliefs, social obligations, and the meaning of tradition as a guideline for life have proven to be the main pillars in framing the harmony of the ummah. The novelty of this research lies in the identification of the role of customary-based religious social capital as a cultural mechanism in forming active tolerance in rural pluralistic communities.